Poverty: Definition, Factors, Measure, and Approach - Nand Kishor Kumar; Man Bahadur Sunuwar (International Journal of Humanities, Education, and Social Sciences, 2026)
Poverty remains a complex and multidimensional phenomenon that cannot be effectively addressed through a single policy instrument or a purely income-based perspective. This study examines poverty as a structural and human development challenge and emphasizes the need for comprehensive and integrated solutions to reduce its incidence and improve overall well-being. The analysis highlights that effective poverty reduction depends on the interaction of inclusive economic growth, social protection, good governance, and the empowerment of marginalized groups. It further underscores that a balanced combination of income-based and human-centered approaches is essential for addressing the multiple dimensions of deprivation and for promoting sustainable development. The study concludes that poverty alleviation strategies must move beyond narrow monetary measures and adopt a more integrated framework that strengthens livelihoods, expands social inclusion, and enhances the quality of life for all.